Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species - Alwin-Kownacka, Alicja; Szadziewski, Ryszard; Szwedo, Jacek (Zootaxa, 2016)
Middle East predatory biting midges of the tribe Ceratopogonini, covering 22 species of 7 genera are reviewed. Three new species are described and illustrated: Allohelea israelensis Szadziewski & Alwin sp. nov., Kolenohelea levantica Szadziewski & Alwin sp. nov. and Serromyia galilaeae Szadziewski & Alwin sp. nov. The genus Boreohelea Clastrier & Delécolle, 1990 syn. nov. is recognized as a junior synonym of Allohelea Kieffer, 1917. Thysanognathus nilogenes Kieffer, 1925 syn. nov. from Egypt is a junior synonym of Alluaudomyia melanosticta (Ingram & Macfie, 1922). Keys to identification of subfamilies, tribes, genera and species of Ceratopogonini of the Middle East are also provided.